Paket Intervensi Kesehatan Esensial pada Remaja Putri Sebagai Langkah Memutus Siklus Stunting: Sebuah Tinjauan Literatur: Essential Health Intervention Package for Adolescent Girls as a Step to Break the Stunting Cycle: A Literature Review - Widaryanti, Rahayu; Dana, Yoga Adhi; Istiqomah, Dedeh; Nugraheni, Sri Achadi (Amerta Nutrition, 2024)
Background: In Indonesia, approximately 32% of Indonesian adolescents experience anemia, if it not addressed effectively, adolescents suffering anemia pose a risk of resulting in stunted growth in their future offspring. Addressing nutritional issues including anemia in adolescence is a crucial step in efforts to break the cycle of stunting. Objectives: This study aimed to review and analyze various essential health interventions for adolescent girls as a strategy to break the cycle of stunting through a comprehensive article review. Methods: Literature was collected from four English-language databases: Scopus, PubMed, Springer Link, and EBSCOhost published from January 2013 to November 2023. The authors conducted article searching using the keywords "Adolescent girl" OR "teenage girl" OR "young woman" AND Intervention AND stunting. Inclusion criteria for this study encompassed community- or population-based research utilizing cross-sectional, cohort, and experimental methods. Exclusion criteria included systematic literature reviews and studies that did not report relevant findings. Ultimately, 10 articles were reviewed from a total of 4,596 articles identified, following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)2020 checklist. Discussions: The health intervention package designed for adolescent girls to prevent stunting includes health education delivered through various methods such as PowerPoint presentations, videos, booklets, and comics, along with the implementation of youth integrated post (posyandu) and community or school-based health intervention. Health promotion materials cover diet, personal hygiene, and supplementation of micronutrients and macronutrients. Conclusions: Implementing the appropriate package of essential health interventions constitutes an effective and efficient approach to break the cycle of stunting.